Structural changes in the agricultural sector - Tyapkina Maria (EDP Sciences, 2021)
The article aims to describe structural changes in the agrarian sector of Irkutsk region caused by the government support for small businesses, simplified procedures for farm registering, accounting for property and production results, and taxation, which contributed to the development of peasant farming. The government support is required, but it can change the structure of areas and gross grain crops since peasant farms increase quantitative indicators rather than improve quality parameters (yield, productivity). This is especially true for the animal husbandry sector. With changes in government policies and decreasing government support, it will be difficult for individual farms to exist, since they lag behind collective farms in terms of maneuverability, financial capabilities, production and credit resources, which can cause new structural changes in a benefit for agricultural holdings. The government policy aimed at preserving the traditional way of life of the rural population should stimulate both the development of rural areas and agricultural production, and prevent the disintegration of collective farms that have competitive advantages